A Facile Process to Fabricate Phosphorus/Carbon Xerogel Composite as Anode for Sodium Ion Batteries. Issue 8 (19th August 2021) - Deng, Changyu; Lu, Wei
Abstract : Sodium ion batteries have become popular due to their low cost. Among the possible anode materials for sodium ion batteries, phosphorus has great potential owing to its high theoretical capacity. Previous research that yielded high capacity and long duration for a phosphorus anode used expensive materials such as black phosphorus (BP) and phosphorene. To take advantage of the low cost of sodium ion batteries, we report a simple and low-cost method to fabricate the anode: condensing red phosphorus on carbon xerogel. Even with a large particle size (∼ 50 m) and a high mass loading (2 mg cm −2 ), the composite cycled at 100 mA g −1 yielded a capacity of 357 mA g −1 or 2498 mAh g P − 1 based on phosphorus after subtracting the contribution of carbon. The average coulombic efficiency is as high as 99.4%. When cycled at 200 mA g −1, it yielded a capacity of 242 mAh g −1 or 1723 mAh g P − 1, with average degradation rate only 0.06% in 80 cycles. Our research provides an innovative approach to synthesize anodes for sodium ion batteries at extremely low cost, with performance exceeding or comparable to state-of-the-art materials, which will promote their commercialization.